1999
DOI: 10.1046/j.1523-1755.1999.00266.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of recombinant human erythropoietin on endothelial cell apoptosis

Abstract: These results suggest that rHuEPO prevents LPS-induced apoptosis in endothelial cells. This protective effect could be an important factor in the action of rHuEPO on vascular endothelium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
67
1
2

Year Published

2002
2002
2013
2013

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(73 citation statements)
references
References 21 publications
3
67
1
2
Order By: Relevance
“…CD34+/Flk-1 (also known KDR or VEGFR2) positive cells are hematopoietic progenitor cells that may differentiate into endothelial cells and contribute to neovascularization and vascular repair (197,198). Epo promotes proliferation (40,196), inhibits apoptosis (199), and facilitates differentiation of EPCs (200)(201)(202)(203). Furthermore, Epo induces mobilization of EPCs into the circulation (204,205), and their homing (155,206,207).…”
Section: Epo In Treatment Of Cardiovascular Diseasesmentioning
confidence: 99%
“…CD34+/Flk-1 (also known KDR or VEGFR2) positive cells are hematopoietic progenitor cells that may differentiate into endothelial cells and contribute to neovascularization and vascular repair (197,198). Epo promotes proliferation (40,196), inhibits apoptosis (199), and facilitates differentiation of EPCs (200)(201)(202)(203). Furthermore, Epo induces mobilization of EPCs into the circulation (204,205), and their homing (155,206,207).…”
Section: Epo In Treatment Of Cardiovascular Diseasesmentioning
confidence: 99%
“…51 Erythropoietin has been shown to inhibit apoptosis in cultured bovine aortic endothelial cells in response to endotoxin. 52 Initial experience with aurintricarboxylic acid, a potent inhibitor of apoptosis, indicates that it inhibits TTP-plasma induced endothelial apoptosis in vitro, but its toxicity appears to preclude its clinical use. 53 TNF␣ appears to be an important cytokine mediator of GVHD and may also be important in the initiation of TA-TMA.…”
Section: Future Directions In Diagnosis and Management Of Ta-tmamentioning
confidence: 99%
“…Several studies have suggested that Epo might stimulate angiogenesis by acting to promote proliferation and/or migration of endothelial cells (Anagnostou et al, 1990;Ribatti et al, 1999), inhibiting apoptosis of endothelial cells (Carlini et al, 1999), or by increasing MMP-2 secretion (Ribatti et al, 1999). rEpo has also been shown to increase the number of circulating endothelial cells and endothelial cell progenitors in preclinical models (Monestiroli et al, 2001) and human breast cancer and lymphoma models ).…”
mentioning
confidence: 99%